2019
DOI: 10.1111/jicd.12395
|View full text |Cite
|
Sign up to set email alerts
|

Unerupted permanent incisors and associated dental anomalies

Abstract: Aim:The aim of the present study was to investigate the association between unerupted permanent incisors and dental anomalies among children and adolescents. Methods:The clinical records of patients between January 2005 and December 2014 were retrieved to identify those with unerupted permanent incisors. A retrospective audit on the presence or absence of any dental anomalies was done from all available records of the included patients. Results:A total of 266 patients with 320 unerupted permanent incisors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Akkuc et al observed in their study, an incidence of maxillary permanent canine impaction of 3.43%, with resorption of maxillary lateral incisors in 33% of cases. Ectopic eruption of the permanent canine can also be related to the noneruption of the permanent lateral incisor [36]. In addition to concerns regarding the consequences of ectopic eruption in the involvement of oral there are also psychological consequences, with an impact on the quality of patients' lives, as also concluded by Masood et al This was noted in the patient in the present study because of the evident change in the smile line after the loss of the permanent central incisor.…”
Section: Case Reports In Dentistrysupporting
confidence: 75%
See 1 more Smart Citation
“…Akkuc et al observed in their study, an incidence of maxillary permanent canine impaction of 3.43%, with resorption of maxillary lateral incisors in 33% of cases. Ectopic eruption of the permanent canine can also be related to the noneruption of the permanent lateral incisor [36]. In addition to concerns regarding the consequences of ectopic eruption in the involvement of oral there are also psychological consequences, with an impact on the quality of patients' lives, as also concluded by Masood et al This was noted in the patient in the present study because of the evident change in the smile line after the loss of the permanent central incisor.…”
Section: Case Reports In Dentistrysupporting
confidence: 75%
“…Akkuc et al observed in their study, an incidence of maxillary permanent canine impaction of 3.43%, with resorption of maxillary lateral incisors in 33% of cases. Ectopic eruption of the permanent canine can also be related to the non-eruption of the permanent lateral incisor [ 36 ].…”
Section: Discussionmentioning
confidence: 99%